2023
DOI: 10.3390/su15086562
|View full text |Cite
|
Sign up to set email alerts
|

Slot-Die Coated Copper Indium Disulfide as Hole-Transport Material for Perovskite Solar Cells

Abstract: Perovskite photovoltaics have the potential to significantly lower the cost of producing solar energy. However, this depends on the ability of the perovskite thin film and other layers in the solar cell to be deposited using large-scale techniques such as slot-die coating without sacrificing efficiency. In perovskite solar cells (PSCs), Spiro-OMeTAD, a small molecule-based organic semiconductor, is commonly used as the benchmark hole transport material (HTL). Despite its effective performance, the multi-step s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…However, in our study, we observed that the gap between the slot die head and the substrate had minimal impact on sample thickness. This observation aligns with findings from other reports, which emphasize the importance of maintaining optimal meniscus liquid volume stability while minimizing the influence of substrate surface roughness [40][41][42]. As a result, we opted for a gap height of 200 micrometers in our research.…”
Section: Optimization Of Slot-die Printing Parameterssupporting
confidence: 84%
“…However, in our study, we observed that the gap between the slot die head and the substrate had minimal impact on sample thickness. This observation aligns with findings from other reports, which emphasize the importance of maintaining optimal meniscus liquid volume stability while minimizing the influence of substrate surface roughness [40][41][42]. As a result, we opted for a gap height of 200 micrometers in our research.…”
Section: Optimization Of Slot-die Printing Parameterssupporting
confidence: 84%